Burden of digestive diseases in Portugal: trends in hospitalizations between 2000 and 2010. Issue 3 (March 2015) - Pinho, Inês; Santos, João Vasco; Dinis-Ribeiro, Mário; Freitas, Alberto
Abstract : Objective: Data on the burden of gastrointestinal diseases are incomplete, particularly in Southern European countries. The aim of this study was to estimate the burden of digestive diseases in Portugal. Patients and methods: This was a retrospective observational study based on the national hospitalizations database that identified all consecutive episodes with a first diagnosis of a digestive disease between 2000 and 2010 using ICD-9-CM codes. Comparative analyses were carried out to assess hospitalization trends of major indicators over time and across regions. Results: More than 75 000 deaths attributable to digestive diseases were observed, representing 16% of the overall in-hospital mortality. Over half of these (59%) were premature deaths (in patients <75 years of age). Biliary tract disease was the most common digestive disorder leading to hospitalization (249 817 episodes, 5210 episodes of acute stone-related cholecystitis in 2010, with an 11% increase compared with 2000). Gastric cancer was responsible for the highest number of in-hospital deaths (10 278) and alcohol-related liver disorders accounted for the highest in-hospital premature deaths (7572). Both costs and the in-hospital mortality rate for major digestive diseases showed a significant positive relation with progression of time ( β =0.195, P <0.001); however, when adjusted for age, this was not significant. Significant positive associations were found between age and in-hospital mortality (odds ratio=1.032, P <0.001) and between costs and in-hospital mortality (odds ratio=1.054, P <0.001). Conclusion: In Portugal, digestive diseases represent a major burden, with evidence of an increasing trend. An ageing population contributes strongly towards this increase, placing further demands on healthcare organizations. Diseases such as gastric cancer, biliary tract disease and alcohol-related liver disorders may require particular attention.